2018
DOI: 10.3390/su10082892
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Strategies for Competitive Water Supply Chains under Different Power Structures: An Application to the South-to-North Water Diversion Project in China

Abstract: Abstract:Under two different power structures, where the supplier and the distributor, respectively, are modeled as the leader, this paper studies water pricing strategies in two competing water resources supply chains. We assume that each water supply chain consists of a risk-neutral water supplier and a risk-neutral water distributor. We build different decision models for two competitive water resources supply chains, derive the optimal decision strategies for the water supply chain members, and analyze how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…These issues are under the guidance of retailers rather than under the same authorization. However, with some retailers, such as Wal Mart and Carrefour, entering the Chinese market, the market power of retailers has been expanding, and the supply chain mode dominated by the retailer has gradually emerged [50]. For example, in today's society, there are not only power control structures dominated by manufacturers, such as Lenovo and Haier, but also power control structures dominated by a retailer, such as Suning and Gome.…”
Section: Operation and Revenue-sharing In A Low-carbon Supply Chainmentioning
confidence: 99%
“…These issues are under the guidance of retailers rather than under the same authorization. However, with some retailers, such as Wal Mart and Carrefour, entering the Chinese market, the market power of retailers has been expanding, and the supply chain mode dominated by the retailer has gradually emerged [50]. For example, in today's society, there are not only power control structures dominated by manufacturers, such as Lenovo and Haier, but also power control structures dominated by a retailer, such as Suning and Gome.…”
Section: Operation and Revenue-sharing In A Low-carbon Supply Chainmentioning
confidence: 99%
“…For our research topic, we should also deeply explore recent literature in terms of the impact of risk preference on water supply chain. Du et al [44] considered risk preference of water supplier and water distributor in order to study water pricing strategies in two competitive water supply chains. However, they assumed that the water supplier and water distributor were risk-neutral and acted rationally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was not for the lake of the SNWD water, but because of the water-dispatching rule, i.e., the SNWD water was only used for domestic purpose. Research showed that the cost of SNWD water is 2.21 Yuan/m 3 [27][28][29]. It is the most expensive among all kinds of water resources.…”
Section: The Guarantee Effect Of the Snwd Projectmentioning
confidence: 99%